Penerapan Algoritma Naïve Bayes Dalam Memprediksi Pengusulan Penghapusan Peralatan dan Mesin Kantor - Isfida Tyas Monowati; Resad Setyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Badan Keuangan dan Aset Daerah (BKAD) of Banyumas Regency is the implementing element of the regional government in the areas of regional taxes, financial management and assets led by a Head of Agency who is located under and is responsible to the Mayor through the Regional Secretary. Badan Keuangan dan Aset Daerah (BKAD) of Banyumas Regency. has various types of Kartu Inventaris Barang (KIB) which are still not well managed, namely office equipment and machines, so a decision support system is needed to predict the removal of office equipment and machines. The use of data mining is done to help find out what equipment and machines are still suitable for use or not suitable for use every year in an institution. Data collection that is not careful in managing data can cause the allocation of funds not to be focused on replacing goods that are no longer feasible. Searching for information on datasets can be done with one of the Data Mining methods, namely the Naïve Bayes Algorithm using RapidMiner tools. The data set consists of 24 records with 3 attributes, namely the year of purchase or procurement, materials and conditions. The dataset is processed using the Naive Bayes algorithm and tested using a confusion matrix. An accuracy value of 100% is obtained which is categorized as a good classification.